Phytochemistry investigation and antioxidant activity of four edible Verbenaceae of Burkina Faso - BANGOU Mindiédiba Jean; REYES-MARTÍNEZ Alfonso; COULIDIATI Tangbadioa Hervé; MEGALIZZI Véronique; NACOULMA Odile Germaine (International Journal of Phytomedicine, 2017)
Lantana rhodesiensis Moldenke, Lippia chevalieri Moldenke, Vitex diversifolia Bak and Vitex doniana Sweet are four species of Verbenaceae family widely used in traditional medicines in Burkina. The aim of this investigation was to study the chromatographic profile of phenols acids and that of the flavonoids as well as the antioxidants activities. Then, three types of extraction were made: acetonic (100%), decoction, ethanol-water(80/20 + 20/80); and fractions of ethanol-water which arehexane fraction (HF), ethyl acetate fraction (EAF), butanol fraction (BF) and aqueous fraction (AqF) of each species. These evaluations were supplemented by the quantification of the metal ions and the characterization by atomic absorption and HPLC-DAD methods of totals phenols acids and totals flavonoids.The whole of these proportioning was directed against the antioxidant activity through the anti-DPPH* (free radical scavenging activity), anti-TAC (total antioxidant capacity) and anti-IRP(iron reducing power).36 flavonoids on 41 were highlighted by the HPLC-DAD method. A derivative glycosylate of quercetin was detected in the V. diversifolia extracts. L. chevalieri presented the strongest value in terms of ions content with a 55.88 g/kg of calcium.In terms of antioxidant activity, L. rhodesiensis and L. chevalieri presented the best activities on total antioxidant activity and anti-DPPH, and iron reducing power respectively.It’s arise that decoction extract have the best’s activities and can justify the traditional uses.